(untitled) (International Journal of Food and Nutritional Sciences, 2019)
The aim of this study is to explore with the innovative teaching methods such as blended and integrated methods of teaching in language learning to higher education HE students. The observations are also made by scrutinizing their achievements in the tasks and their motivational levels towards learning the tasks. The illustration is exclusively designed for the select higher education HE students. The select group of learners from KL deemed to be university. The experimental group is given a questionnaire on English learning proficiency through a computerized program in the integrated method. Concepts like vocabulary learning, spell check, word pronunciation and accent are given to this group of people. Hence, the research explored that the virtual learning and integrated teaching methods with blended and flipped learning methods gives better results than traditional and personal teaching methods. The statistical analysis revealed the significance and importance of blended and integrated methods of teaching. The importance of information communication technologies (ICT) is increasing day by day. Moreover, the COVID Pandemic has become a challenge to the traditional teaching and learning methods. Hence, the terms like teacher, class room teaching and student have been replaced with the terms such as learner-centric approach, interactive and collaborative learning with integrating technological teaching methods.